REKAYASA SISTEM PENANGANAN KLAIM PERBAIKAN MOBIL PADA BENGKEL DENGAN METODE KARAKTERISTIK RELEVANSI - Indra Hiswara; Rahmad Fitri; Helya Santi (Institut Teknologi dan Bisnis (ITB) Swadharma, 2022)
PT Jakarta Teknologi Utama is a company engaged in car body repair services or body repair specialists, which is the official workshop of a company engaged in insurance. The repair service process at this time still adheres to the old system, which only prioritizes the quality of repairing the vehicle, without paying attention to customer comfort from other factors. Based on the background of the problem formulation, how to design a claim handling information system, so that the application can not only record claims data recording activities but can also produce accurate reports on claims from customers. This research aims to design a claim handling information system at the workshop. The results achieved are in the form of an application consisting of inputs, processes, and reports, the design runs as planned